Massive lymphorrhoea as a rare complication of total thyroidectomy with left-sided neck dissection – a case report - Nowaczyk, Piotr; Murawa, Dawid; Połom, Karol; Wybrański, Wojciech (Contemporary Oncology/Współczesna Onkologia, 2009)
Thyroid cancer accounts for 1% of human malignant neoplasms and is the most frequent tumour of endocrine glands. Treatment of this neoplasm is combined and comprises thyroidectomy and radioiodine therapy. The most common thyroidectomy complications include: recurrent laryngeal nerve palsy, upper laryngeal nerve palsy, hypoparathyroidism, haemorrhage, dysphagia and surgical site infection. This paper describes a case of papillary thyroid carcinoma treated with total thyroidectomy and left-sided neck dissection. In the postoperative course lymphorrhoea, a rare complication of thyroidectomy, occurred. Treatment composed of total parenteral nutrition and octreotide was implemented and on the fourth postoperative day a spontaneous stoppage of chyle leakage was observed. According to current standards, the treatment of postoperative lymphorrhoea can be either conservative or surgical. The choice of treatment method is made in accordance with chyle volume, length of lymphorrhoea and patient condition. Indications for surgical therapy are not clear. It is a high risk procedure (technical problems because of chemical inflammation in the operated area), with the possibility of causing other, more serious complications. Moreover, there is no medical evidence that surgical treatment is better than conservative therapy, even in the case of persistent, high-volume chyle leaks. Considering all the above facts the treatment method applied to our patient seems to be optimal